The Vitality of Mother Tongues in a Multilingual Society in Dieng, Central Java - Nunung Sitaresmi; Meilani Puji Astini; Lilis Siti Sulistyaningsih; Isah Cahyani; Rahmawati, Rahmawati (Jurnal Arbitrer, 2023)
Multilingual conditions can threaten the mother tongue in a tourism area because most people use other languages when interacting with tourists. Thus, it can hamper the inheritance of the mother tongue or even replace it with another language. This study used a sociolinguistic theoretical approach to measure the mother tongue’s vitality level in a multilingual community in Dieng, Central Java. This descriptive study used a mixed method. Data were collected from interviews with 53 informants and with the help of a research instrument namely the Interview Package of “Basa Urang”. Data were analyzed based on Miles dan Huberman’s model (1984), covering data collection, reduction, presentation, and drawing conclusions. The study results showed that the vitality of the mother tongue in the multilingual community in Dieng, Central Java is in the vulnerable category as the mother tongue is only used in the domestic domain. This is proven by the percentage level of mother tongue use based on patterns ‘with’, patterns ‘in’, and patterns ‘for’. The main factors causing the low vitality of the mother tongue in the multilingual community in this area are economic and educational. This study describes the condition of each living language in a multilingual society in Dieng, Central Jawa. This study provides quite large implications in describing the vitality of mother tongues in a multilingual society in Dieng, Central Java, but further studies are needed to get a deeper understanding of the implications.